Bioinformatics Analysis of Hub Genes Involved in Alcohol-Related Hemifacial Microsomia Pathogenesis. Issue 6 (29th September 2022) - Ma, Lunkun; Zhao, Shanbaga; Xu, Xi; Shu, Kaiyi; Li, Xiyuan; Liang, Yingxiang; Liu, Bingyang; Huang, Changjin; Zhang, Zhiyong
Abstract : Objective: Alcohol is a recognized teratogen, and alcohol exposure increases the risk for hemifacial microsomia (HFM) of the fetus during maternal pregnancy. The present study aimed to explore potential mechanisms and verify hub genes of HFM associated with alcohol by bioinformatics methods. Methods: First, HFM and alcohol pathogenic genes were obtained. Thereafter, a protein-protein interactional (PPI) network was constructed. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses and molecular complex detection were performed by Metascape. Finally, we used the cytoHubba plugin to screen the hub genes. Results: A total of 43 HFM genes and 50 optimal alcohol candidate genes were selected. The PPI networks for pathogenic genes contained 93 nodes and 503 edges. Functional enrichment analysis largely focused on tissue formation and development. Two modules were identified from the PPI network, and 10 hub genes were screened out. The genes most relevant to alcohol-induced HFM pathogenesis included CTNNB1, TP53, MYC, HDAC1, and SOX2. Conclusions: This study identified some significant hub genes, pathways, and modules of HFM related to alcohol by bioinformatics analyses. Our results suggest that the CTNNB1, TP53, MYC, HDAC1, and SOX B1 gene subfamilies may have played a major role in alcohol-induced HFM.